Macrocycle Unidirectional Transport Along a Linear Molecule by a Two‐Step Chemical Reaction Sequence - Aldo C. Catalán; Lucio Peña‐Zarate; Ruy Cervantes; Alberto Vela; Jorge Tiburcio (ChemistryOpen)
Abstract Chemical systems displaying directional motions are relevant to the operation of artificial molecular machines. Herein we present the functioning of a molecule capable of transporting a cyclic species in a preferential direction. Our system is based on a linear, non‐symmetric, positively charged molecule. This cation integrates into its structure two different reactive regions. On one side features a bulky ester group that can be exchanged by a smaller substituent; the other extreme contains an acid/base responsive moiety that plays a dual role, as part of the recognition motif and as a terminal group. In the acidic state, a dibenzo‐24‐crown‐8 ether slides into the linear component attracted by the positively charged recognition site. It does this selectively through the extreme that contains the azepanium group, since the other side is sterically hindered. After base addition, intermolecular interactions are lost; however, the macrocycle is unable to escape from the linear component since the energy barrier to slide over the neutral azepane is too large. Therefore, a metastable mechanically interlocked molecule is formed. A second reaction, now on the ester functionality, exchanges the bulky mesityl for a methyl group, small enough to allow macrocycle dissociation, completing the directional transit of the ring along the track.